Economic Growth and The Potential of Corruption’s Existence: The Case of Distracted Directors in Saudi Arabia - Aljaaidi, Khaled Salmen (International Journal of Membrane Science and Technology, 2023)
The objective of this study is to examine the impact of distracted directors on the economic growth of companies listed in Saudi Arabia for the period 2012-2019. The final sample consists of 509 firm-year observations. This study integrated the return on assets (ROA), return on equity (ROE), and profit margin ratio (PMR) to establish a composite score indicating the economic growth of companies (EG). Specifically, this study focused on the analysis of firm performance through the utilization of three distinct individual models as well as a composite model. The composite measure (EG) was derived using factor analysis, a statistical technique, to assess companies’ growth. Furthermore, this study used the hypotheses derived from well-established theories to explain the relationship between distracted directors and the economic growth of companies. These include the social network theory, the reputational hypothesis, the agency-based busyness hypothesis, and the resource-dependence theory. The social network theory, reputational hypothesis, and resource-dependence theory all posit positive correlations, whereas the busyness hypothesis posits a negative correlation. This study posits a potential correlation without specifying its direction because of the conflicting theories that attempt to predict the relationship, as well as the inconsistent results reported in previous empirical research. The study’s findings provided support for the agency-based busyness hypothesis, as they revealed a negative association between distracted directors and economic growth. The findings of this study have significant implications for the corporate governance policymakers in Saudi Arabia, particularly in relation to the understanding of how distracted directors sitting on the board may indicate potential corruption that, in turn, has a negative impact on the economic growth of companies.